'Honeycomb' nanotube assembly based on thiacalix[4]arene derivatives by weak interactions1. Issue 40 (28th October 2015) - Wang, Wei; Yang, Weiping; Guo, Rong; Gong, Shuling
<x xml:space="preserve">Abstract</x> Crystallisation of six thiacalix[4]arene derivatives from hexane–chloroform leads to 'honeycomb' nanotube architectures and each tubular stack is surrounded by six close tubular neighbours via weak interactions, such as S⋯π interactions, C–H⋯π interactions, and so on.